Uniform Civil Code, Legal Pluralism and Inheritance Rights… of Tribal Indian Women - Singh, Jyoti (PRAWO i WIĘŹ, 2024)
The 42nd Amendment to the Indian Constitution heralded India as a „Sovereign, Socialist, Secular Democratic Republic”. It initiated a constitutional narrative that has sparked ongoing debates and scrutiny regarding the true essence of India’s secularism. As the nation approaches the 2024 general elections, the ruling party has discussed the potential implementation of the Uniform Civil Code at the forefront of political discourse. In this commentary, the authors discuss legal pluralism in India and the impact of the introduction of a uniform civil code on on customary laws of tribes, placing special emphasis on the inheritance rights of tribal women. The paper also discusses the approach of the higher courts in securing property rights for tribal women in the absence of such a code.